Analisis Pengaruh Jumlah Penduduk dan Indeks Pembangunan Manusia (IPM) terhadap Kemiskinan di Provinsi Jambi - Amelia Sari; M. Afdal Samsuddin (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study analyzes the effect of population and Human Development Index (HDI) on poverty in Jambi Province in the period 2018–2024. Using panel data from 11 districts/cities and regression methods with the best approach Random Effect Model (REM), the results show that poverty in Jambi tends to fluctuate. Tanjung Jabung Timur has the highest poverty rate, while Sungai Penuh City has the lowest. This study provides empirical understanding to support the formulation of more targeted poverty alleviation policies at the regional level.